Optimizing agronomic requirements of arvi (Colocasia esculenta L. Schott) under different agroforestry tree species in Punjab - Kaur, Navneet; Singh, Baljit; Gill, R.I.S. (Indian Journal of Agroforestry, 2020)
Arvi (Colocasia esculenta) is a shade tolerant crop. The extent of shade that is required for its optimum growth and yield under agroforestry system needs to be established. The growth and productivity of understorey crops varies under different tree plantations owing to difference in nature of tree-crop interactions. The present study was done to work out the agronomic requirements of arvi intercropped under different aged block plantation of poplar (Populus deltoides), dek (Melia composita), toon (Toona ciliata) and maharukh (Ailanthus excelsa) established at 5 x 4 m spacing during 2006 and 2007. The results showed that the yield of arvi was significantly less under poplar and dek as compared to yield under maharukh plantation. This could be attributed due to more height and crown spread of poplar and dek plantations. In general, the crop sown on ridges gave higher yield compared to the crop sown on flat beds. The arvi sown on ridges with additional seed (8.75 q/ha) and fertilizers (155 kg N, 62.5 kg P2O5 and 62.5 kg K2O/ha) gave significantly higher yield (161.4 q/ha) as compared with crop sown on flat beds with recommended seed rate and fertilizers under higher aged plantations.